2008
DOI: 10.2214/ajr.07.3176
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Comparison of Contrast Media Concentrations for Combined Abdominal and Thoracic MDCT

Abstract: Given equivalent iodine load and delivery rate, the use of 300 mg I/mL contrast medium results in better contrast enhancement than use of 370 mg I/mL contrast medium in CT of the chest. For the portal venous phase of CT of the abdomen, there was no significant difference in contrast enhancement for the two concentrations of iodine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 30 publications
6
28
3
Order By: Relevance
“…Our results show significantly higher attenuation values for the 300 mgI/ml compared with the 370 and 400 mgI/ml contrast medium. Similar results have been reported previously in other, partly intra-individual, studies [7,[21][22][23]. A possible explanation for the observation of higher mean attenuation values for CM with lower iodine concentrations, especially during the early phase of the CT, is that flow characteristics differ because of viscosity.…”
Section: Discussionsupporting
confidence: 90%
“…Our results show significantly higher attenuation values for the 300 mgI/ml compared with the 370 and 400 mgI/ml contrast medium. Similar results have been reported previously in other, partly intra-individual, studies [7,[21][22][23]. A possible explanation for the observation of higher mean attenuation values for CM with lower iodine concentrations, especially during the early phase of the CT, is that flow characteristics differ because of viscosity.…”
Section: Discussionsupporting
confidence: 90%
“…Our data are in accordance with those of previous investigations in patients with or without cirrhosis [23][24][25] and support the notion that the total amount of iodine, and not the iodine delivery rate, is a major determinant of vascular and parenchymal enhancement during the hepatic parenchymal phase [26].…”
Section: Effect Of Contrast Materials Iodine Concentrations During LIVsupporting
confidence: 93%
“…However, a study by Awai et al in abdominal CT, with a very similar set-up as the aforementioned study by Suzuki et al, did find a benefit for rapid administration of lower concentration contrast medium [19]. Also, a recent intra-individual comparison in combined thoraco-abdominal CT by Behrendt et al found a better enhancement in the thoracic vessels for contrast medium with a concentration of 300 mg I/ml compared with that with a concentration of 370 mg I/ml [20]. It is unclear why our study and the studies by Awai et al and by Behrendt et al did detect a difference in arterial enhancement in favour of the lower concentration contrast medium while the other studies did not.…”
Section: Discussionmentioning
confidence: 72%